Durability of concrete containing laterite aggregate as partial coarse aggregate replacement - Gopi, Vesuvapateran (2013)
The most common type of coarse aggregate used for making concrete in Malaysia is crushed granite. Due to high demand of concrete, the. granite aggregates used in construction industry depleting every year and might lead to increase in granite aggregates price. Therefore, studies need to be conducted to integrate other types of aggregate as partial coarse aggregate replacement in order to avoid aggregate depletion issue and environmental problem that would arise due to excessive use of this material. In the path to overcome this problem Malaysian researchers are conducting research on new construction materials with potential as coarse aggregate replacement in concrete. This thesis presents an experimental study on the effect of laterite aggregate content as partial coarse aggregate replacement towards the behavior of concrete in term of resistance to acid attack, corrosion attack as well as its moisture absorption properties. Mixes consisting a range of laterite aggregate content from (0 - 50%) was use to produce specimens that placed in water curing for 28 days before subjected to durability test. The entire experimental work was carried out according to existing standard. The results of the test conducted reveal that the resistance of concrete towards acid and corrosion decreases with increasing of laterite aggregate content in concrete. Furthermore, the moisture absorption tests indicate concrete with higher laterite aggregate content has high moisture absorption properties.